INTERNALISASI NILAI KARAKTER ISLAM MELALUI PARTISIPASI AKTIF REMAJA MASJID PADA GENERASI Z DI PEDESAAN MADURA - Fahriyah, Walidatul; Zainuddin, Zainuddin (Program Studi Pendidikan Agama Islam Tarbiyah IAI Muhammadiyah Bima, 2026)
The development of digital technology presents unique challenges in the formation of Islamic character in Generation Z, so the role of religious institutions that are able to provide guidance based on values ​​and social experiences is needed. Mosques not only function as places of worship, but also as centers of character education through the active involvement of mosque youth. The purpose of this study is to analyze the role of mosque youth as a means of Islamic character education for Generation Z in Pandiyen Hamlet, Sampang Regency, Madura. This study uses a qualitative approach with a field research type. Data collection techniques were carried out through observation, interviews, and documentation, while the validity of the data was tested through triangulation of sources and techniques. The results show that mosque youth play an active role in religious and social activities, such as congregational prayer, Barzanji recitation, book studies, Islamic holiday commemorations, and social community activities. This role contributes to the formation of Islamic character in Generation Z through habituation, role models, and real-life experiences, although they still face obstacles such as the influence of digital technology, limited time, and differences in levels of religious awareness. These findings indicate that mosque youth have a strategic role as a medium for contextual and sustainable Islamic character education in the community.